1999
DOI: 10.1017/s1355838299991616
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of the avian leukemia virus constitutive transport element

Abstract: The observation that cells restrict the nuclear export of incompletely spliced transcripts via the canonical nuclear mRNA export pathway implies that all retroviruses should have evolved a way to direct the unspliced form of their genomic RNA into an alternate export pathway. While the Crm1-dependent pathway used by complex retroviruses to export incompletely spliced viral transcripts is now fairly well understood, less is known about how simple retroviruses accomplish this task. However, the Mason-Pfizer monk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 31 publications
3
42
0
Order By: Relevance
“…In addition to splicing enhancers and repressors, there are also RNA sequence elements that allow transport of unspliced RNAs to the cytoplasm (261)(262)(263)(264)(265). Some of these transport elements are constitutive, interacting directly with cellular factors (266)(267)(268)(269)(270)(271). Other elements interact with viral proteins, such as HIV Rev, to allow viral control of the nuclear export process (264).…”
Section: Retroviral Splicing and The Balance Of Splicing And Transportmentioning
confidence: 99%
“…In addition to splicing enhancers and repressors, there are also RNA sequence elements that allow transport of unspliced RNAs to the cytoplasm (261)(262)(263)(264)(265). Some of these transport elements are constitutive, interacting directly with cellular factors (266)(267)(268)(269)(270)(271). Other elements interact with viral proteins, such as HIV Rev, to allow viral control of the nuclear export process (264).…”
Section: Retroviral Splicing and The Balance Of Splicing And Transportmentioning
confidence: 99%
“…Furthermore, as reported previously (35) and confirmed in our experiments (unpublished observation), DR deletion does not impart any effect on the RSV replication in rodent cells. On the other hand, it was demonstrated that DR facilitates gRNA egress from the nucleus in mammalian cells (42). Still, there remains the possibility that rodent cells are devoid of some factor(s) needed for interaction with DRs or produce an inhibitor paralyzing DR function, especially at later stages of gRNA processing that follow its export.…”
Section: Discussionmentioning
confidence: 99%
“…Using bioinformatic tools, we have not been able to find any genes outside of the NXF family that possess CTEs based on sequence homology. However, the genomes of several mammalian and endogenous retroviruses have been shown to contain non-homologous elements that function as CTEs in conjunction with Nxf1/Nxt (Ogert and Beemon 1995;Yang and Cullen 1999;Nappi et al 2001;Legiewicz et al 2010;Sakuma et al 2014). In addition, we have previously used retroviral vector "trap" strategies to identify several host cell CTEs that lack apparent homology with the MPMV/NXF1 CTE, but which still function in conjunction with Nxf1/Nxt1 .…”
Section: Nxf1-cte Functional Conservationmentioning
confidence: 99%